2018
DOI: 10.1111/liv.13882
|View full text |Cite
|
Sign up to set email alerts
|

In vitro efficacy of pro‐ and anticoagulant strategies in compensated and acutely ill patients with cirrhosis

Abstract: Background & AimsA simultaneous decline in pro‐ and anticoagulant drivers in patients with liver diseases results in a “rebalanced” haemostatic system, even in acutely ill patients. Nevertheless, both bleeding and thrombotic events are common. Here, we explored efficacy of pro‐ and antihaemostatic strategies in compensated and acutely ill cirrhotics which may be unpredictable given the profound haemostatic changes.MethodsWe tested the effects in vitro of the addition of clinically relevant doses of commonly us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
59
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 42 publications
2
59
0
1
Order By: Relevance
“…An ex vivo study of PCC conducted using blood samples from liver transplant recipients showed that PCC was more effective than FFP in increasing thrombin generation . Similarly, in a study testing the effects of in vitro addition of hemostatic agents using thrombin generation tests, FFP and rFVIIa only modestly increased thrombin generation in patients with compensated and acutely decompensated cirrhosis, whereas PCC increased thrombin generation 2‐fold to 4‐fold in these patients and approximately 2‐fold in healthy individuals . In a clinical study conducted across a range of settings, which included a small cohort of patients with liver disease, PCC therapy was associated with a trend toward a reduction in INR .…”
Section: Discussionmentioning
confidence: 99%
“…An ex vivo study of PCC conducted using blood samples from liver transplant recipients showed that PCC was more effective than FFP in increasing thrombin generation . Similarly, in a study testing the effects of in vitro addition of hemostatic agents using thrombin generation tests, FFP and rFVIIa only modestly increased thrombin generation in patients with compensated and acutely decompensated cirrhosis, whereas PCC increased thrombin generation 2‐fold to 4‐fold in these patients and approximately 2‐fold in healthy individuals . In a clinical study conducted across a range of settings, which included a small cohort of patients with liver disease, PCC therapy was associated with a trend toward a reduction in INR .…”
Section: Discussionmentioning
confidence: 99%
“…4 In vitro experiments have indicated that FFP does not increase coagulation potential in patients with cirrhosis as it supplies both pro-and anticoagulant proteins in equal amounts. 5 As a result, although plasma levels of individual coagulation factors increase and as a consequence the prothrombin time and INR may decrease, actual thrombin generating capacity does not change or may even decrease. Further, in many procedures undertaken in patients with CLD, procedural risk appears lower than generally appreciated.…”
mentioning
confidence: 99%
“…61 Indeed, in vitro studies suggest major differences in the anticoagulant potency of commonly used anticoagulant drugs. 35,62 In addition, the pharmacokinetics of anticoagulant agents may be different in patients with cirrhosis. This might be particularly relevant for direct oral anticoagulants that are partially cleared by liver, and dose adjustments may be required in patients with cirrhosis.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…For example, Lisman et al have demonstrated enhanced in vitro potency of prothrombin complex concentrates in patients with cirrhosis, suggesting dose-reductions may be required for these types of agents. 62 Moreover, it would be important to pay attention to a potential tilt of the fragile balance toward (more) hypercoagulability, if no AT is administered (PCC), or if AT is in insufficient amounts in FFP.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%